ENCOURAGING SUSTAINABLE CONSUMPTION PATTERNS THROUGH MATHEMATICS AND EXPERIMENTAL SCIENCE IN HIGHER EDUCATION - Fernández, M, Albareda S., Fernández, M. Y. & Vidal, S (International Journal of Research Science and Management, 2018)
The United Nations adopted the 2030 Agenda for sustainable development in January 2016 with the aim of improving and achieving what had previously not been possible with the Millennium Development Goals. The role of education and educators of all levels and disciplines is crucial in the quest to advance towards a more sustainable world. At university level, and within the framework of the European Higher Education Area, which proposes an opportunity for change, a sustainable curriculum is not restricted to the inclusion of environmental content in the syllabi of the different subjects taught. However, integrating sustainability into university curricula leads to global changes in the educational process. This change of paradigm, acquires special relevance in preservice teacher training since those future teachers are the ones who will contribute to the formation of the future generation of citizens. This work presents a proposal for introducing sustainability into the University curriculum, through education for responsible consumption in the subjects of mathematics and experimental science of future Primary School teachers at Universitat Internacional de Catalunya. The students were asked to fill in a questionnaire about their consumption habits before and after the educational programme. Changes towards more sustainable attitudes were observed in their routines after the intervention. These results show that through a properly designed and implemented educative proposal, it is possible to introduce changes into the consumption patterns of students. This paper shows an education model that could be transferred and implemented in other educational contexts.